Analisis Yuridis Perjanjian Kawin Pasca Perkawinan Berdasarkan Putusan Mahkamah Konstitusi Nomor 69/Puu-Xiii/2015 - Winsherly Tan (Journal of Judicial Review, 2018)
This undergraduate final project criticizes about the post nuptial agreement, where before the decision of the Constitutional Court Number 69/PUU-XIII/2015 the marriage agreement can only be made before the marriage takes place. The purpose of this study is to determine the legal consequences of making a marriage agreement after marriage and the legal protection against third parties. This research is legal research with normative method, that is literature study and supported by interview result as supporting data. The data has been collected and then processed and analyzed, then prepared and described descriptively by taking conclusions from the results of data analysis. The results obtained from this study are the post-marriage agreement applicable to the parties making the marriage agreement and related third parties, as a result of the law arising out of the marriage agreement after marriage. Third parties must obtain legal protection in all matters related to the marriage agreement after marriage through preventive and repressive action.